Clinical Practice Guidelines for Pancreatic Cancer 2016 From the Japan Pancreas Society: A Synopsis. Issue 5 (May 2017) - Yamaguchi, Koji; Okusaka, Takuji; Shimizu, Kyoko; Furuse, Junji; Ito, Yoshinori; Hanada, Keiji; Shimosegawa, Tooru; Okazaki, Kazuichi
Abstract : Objectives: Clinical Practice Guidelines for Pancreatic Cancer based on Evidence-Based Medicine 2006 were first published by the Japan Pancreas Society, and they were revised to Clinical Practice Guidelines for Pancreatic Cancer 2009 in July 2009 and were further revised to Clinical Practice Guidelines for Pancreatic Cancer 2013 in October 2013. These guidelines were established according to evidence-based medicine. In October 2016, the Clinical Practice Guidelines for Pancreatic Cancer were newly revised in Japanese. Methods: In the revised version, we introduced the concepts of GRADE - grading recommendations assessment, development, and evaluation approach for better understanding of the current guidelines. Results: The guidelines show algorithms for the diagnosis, treatment, and chemotherapy of pancreatic cancer and address 7 subjects: diagnosis, surgical therapy, adjuvant therapy, radiation therapy, chemotherapy, stent therapy, and palliative medicine. They include 51 clinical questions and 76 statements. There are statements corresponding to clinical questions, evidence levels, recommended strengths, and agreement rates. Conclusions: These guidelines represent the most standard clinical and practical management at this time in Japan. This is the English synopsis of the Clinical Practice Guidelines for Pancreatic Cancer 2016 in Japanese, which aims to disseminate the Japanese guidelines worldwide for the introduction of Japanese clinical management of these diseases.